The treatment of severe behavior problems in school settings using a technical assistance model. - Northup, J (1994)
We evaluated the feasibility of local school personnel conducting functional analysis and reinforcement-based treatment procedures within actual classroom settings. Following an initial in-service workshop on functional assessment and differential reinforcement procedures, on-site technical assistance was provided two to four times per month to local school personnel working in transdisciplinary teams. Overall results suggest that local school personnel were able to implement all procedures adequately with periodic technical assistance. In addition, functional analysis was effective in identifying individual maintaining contingencies, the derived treatments were effective, and the results were maintained throughout the approximate 18 months of this investigation.